KUALITAS ORGANOLEPTIK DAN NUTRISI PANCAKE BERBAHAN PISANG HIJAU TANPA TELUR - Pande Made Calvin Agastya K.D; Ni Putu Eka Trisdayanti (JURNAL GASTRONOMI INDONESIA, 2019)
Egg-based pancakes cannot be consumed by people who are allergic to eggsor processed eggs, sensitive to excess protein, and vegetarians. For pancakes to beconsumed by everyone, eggs need to be replaced with vegetable, for example greenbananas. In this study, researchers processed pancakes made from green bananaswithout eggs, and then tested the organoleptic quality and nutrition of these pancakes.The data collection techniques of this study were experiments, organoleptic tests,and laboratory tests (nutrition). For data analysis techniques researchers useddescriptive qualitative. The results of the research are organoleptic quality of greenbanana pancakes which is very good which has a very sweet and savory taste, verygolden brown color, has a very soft texture, is very flavorful of butter and not fishy. Thenutritional quality of pancakes with green bananas without eggs consists of vitaminc of 86.80 milligrams, calories of 212.92 kcal, protein of 6.62gram, fat of 2.96 gramsand carbohydrates of 39.94 grams.